From the heart of the world the elder brothers' warning - Ereira, Alan (BBC, 1991)
The Kogi people are a pre-Columbian civilization in southwest Columbia. They have isolated themselves for 200 years. In this film, they warn the rest of the world that they must adapt environmentally sound practices before it is too late.